Scientists' Warning to Humanity on Threats to Indigenous and Local Knowledge Systems. Issue Volume 41:Issues 2(2021) (July 2021) - Fernández-Llamazares, Álvaro; Lepofsky, Dana; Lertzman, Ken; Armstrong, Chelsey Geralda; Brondizio, Eduardo S.; Gavin, Michael C.; Lyver, Phil O'B.; Nicholas, George P.; Pascua, Pua'ala; Reo, Nicholas J.; Reyes-García, Victoria; Turner, Nancy J.; et al.
The knowledge systems and practices of Indigenous Peoples and local communities play critical roles in safeguarding the biological and cultural diversity of our planet. Globalization, government policies, capitalism, colonialism, and other rapid social-ecological changes threaten the relationships between Indigenous Peoples and local communities and their environments, thereby challenging the continuity and dynamism of Indigenous and Local Knowledge (ILK). In this article, we contribute to the "World Scientists' Warning to Humanity, " issued by the Alliance of World Scientists, by exploring opportunities for sustaining ILK systems on behalf of the future stewardship of our planet. Our warning raises the alarm about the pervasive and ubiquitous erosion of knowledge and practice and the social and ecological consequences of this erosion. While ILK systems can be adaptable and resilient, the foundations of these knowledge systems are compromised by ongoing suppression, misrepresentation, appropriation, assimilation, disconnection, and destruction of biocultural heritage. Three case studies illustrate these processes and how protecting ILK is central to biocultural conservation. We conclude with 15 recommendations that call for the recognition and support of Indigenous Peoples and local communities and their knowledge systems. Enacting these recommendations will entail a transformative and sustained shift in how ILK systems, their knowledge holders, and their multiple expressions in lands and waters are recognized, affirmed, and valued. We appeal for urgent action to support the efforts of Indigenous Peoples and local communities around the world to maintain their knowledge systems, languages, stewardship rights, ties to lands and waters, and the biocultural integrity of their territories—on which we all depend.